Burning the bridge to Ostpolitik? Stress-testing Europe's shift from Russian gas to renewables using a global energy model - Kong Chyong (The Oxford Institute for Energy Studies, 2024)
This study explores the structural shifts in Europe's energy landscape following the loss of over one-third of its natural gas supplies due to the conflict in Ukraine, effectively severing the traditional natural gas trade 'bridge' between Russia and Europe. Amidst Europe's deep integration into global energy markets, this paper assesses the medium-term market and policy implications of transitioning towards renewables and reducing dependency on Russian gas. Using a detailed global energy market model, the analysis delves into the resilience challenges arising from the 2022/23 energy crisis, highlighting Europe's reliance on natural gas for significant energy consumption and the consequent need for diversifying energy flexibility sources. By examining the increased dependency on LNG, which is expected to cover up to 48% of Europe's energy needs in extreme cold scenarios, and the urgent requirement for better electrical interconnections to facilitate cross-border electricity trade, this paper provides comprehensive insights into market implications of the great decoupling from Russia and policy options that could ensure a more resilient, sustainable European energy system amidst geopolitical tensions and the push for decarbonisation.
Keywords: 330; Economic Modelling; energy security; geopolitics of natural gas; global multi-fuel energy market model; Russian Gas; security externalities